UPAYA PEMERINTAH DESA DALAM PENGEMBANGAN POTENSI WISATA PANTAI INDAH KEMANGI PASCA PANDEMI DI KABUPATEN KENDAL - Suwarji; Maulida Putri Rahmawati; Zahrotul Ummah (Journal Publicuho, 2024)
This study aims to determine how to revive tourism objects after the COVID-19 pandemic in 2020. And this study uses the theory of Kotler and Keller's efforts which refer to the marketing mix indicators, namely price efforts, promotion efforts, place efforts, and product efforts. The data collection technique is observation and interviews which are then processed and analyzed qualitatively. The results of this study indicate that the efforts of the Jungsemi Village government in reviving Pantai Indah Kemangi tourism are by collaborating with other parties such as academics, the Ministry of Maritime Affairs and Fisheries (KKP). Carrying out promotions through social media, building facilities and infrastructure. Supporting factors for the Jungsemi Village Government in reviving Pantai Indah Kemangi tourism are the existing attractions and community conditions that support the development of Pantai Indah Kemangi tourism objects and infrastructure that continues to develop. The inhibiting factors are the myth about the mystical basil tomb, road access that is still damaged and Human Resources at the Pantai Indah Kemangi tourist attraction which are inadequate in the tourism sector.